Maine’s Public Estate and Conservation Lands: Brief History and Assessment - Irland, Lloyd (Maine Policy Review, 2018)
In contrast to other northeastern states, the first conservation movement at the turn of the twentieth century passed Maine by. New Deal conservation programs likewise had little impact here, though several seeds were sown. In a state where public access to open rural land and North Woods lakes and rivers was extensively available, there was no perceived need for a public land system. In southern Maine by the 1990s, sprawl and No Trespassing signs became more visible. In the North Woods, large sales of former paper company land shook confidence that public access to land would continue. In a historic burst of activity, state and federal programs, aided by several nongovernmental organizations, made land and easement acquisitions that in a short time brought 21 percent of Maine’s land into its conservation estate. During this period of activity, a number of baffling policy issues were left largely on autopilot; this article closes with a brief and selective list of them.
Keywords: Maine; public lands; conservation easements